MEMBANDINGKAN PEMAHAMAN TERHADAP "PUNISHMENT" PADA RELASI GURU DAN SISWA BERDASARKAN JURUSAN DI KOTA BUKITTINGGI: STUDI INDIGENOUS PSYCHOLOGY - siskahendriyetti09 (CAUSALITA : Journal of Psychology, 2024)
Education gives students access to knowledge and information that has been collected and organized. Punishment is very important to change student behavior in a safe and orderly school environment. This study reveals the types of punishment and the impact of punishment on high school students using an indigenous psychology approach. This research was conducted on 430 high school students in Bukittinggi City. The method used is descriptive qualitative with an indigenous psychology approach, using an open-ended questionnaire with the stages of open coding, axial coding, and selective coding analysis. The results of this study found that the types of punishment that are preferred and make students not burdened are physical punishment, emotional punishment, and procedural punishment. The impact of punishment that is favored and makes students unburdened consists of academic risk, physical impact, and impact on relationships. The types of punishment that students dislike are physical punishment, emotional punishment, administrative punishment, and punishment that has a long-term impact. The impact of students disliking punishment in the form of threats to academics, threats to the self, risk of new negative behaviors, and social risks. The ways students avoid punishments they don't like include compliance, unexpected behavior, and camouflage/fiking.